Bias and its Corrective Action for Homoeopathy Clinical Research (Homoeopathy for All, 2024)
Various bias occurs in clinical trial  research in homeopathy.Clinical trials are experiments  on human beings conducted  scientifically. The objective is to find  out whether, when we do something  to a group of people, it gives you  the desired result in many of them  or not? Some newly devised or  modified regimen is intentionally  applied to people with or without  disease to find out the efficacy and  safety of this regimen. Therefore,  in homeopathy, clinical trials as  the scientific investigation that  examine and evaluate the safety  and efficacy of medicine therapies  in human subjects are randomly  allocated to two groups, known as  the “Experiment” and the “Control”  group. The experimental group  is given the medicine being tested  and the control group is given the  placebo, an inert substance in sugar  pill.
Keywords: Bias; Confounder; Control and Experimental group; Odd Ratio; Random